Kekuatan Akta Jual Beli sebagai Syarat Formal dalam Proses Balik Nama Hak Guna Bangunan dalam Peralihan Hak (Studi Kasus Putusan Pengadilan Negeri Serang Nomor 107/Pdt.G/2024/PN.Srg) - Al Hane Wahdaliansyah (Jurnal Hukum Lex Generalis, 2025)
Land has strategic value in the Indonesian legal system regarding lawful ownership and control. One common land right is the Right to Build (HGB), whose transfer must follow formal procedures, including the making of a Sale and Purchase Deed (AJB). Problems arise when the AJB is not made, as in Decision of the Serang District Court Number 107/Pdt.G/2024/PN. Srg. Research shows the AJB is a mandatory requirement for title transfer but may be set aside through other evidence if it meets the principle of substantive justice. The public is advised to transfer titles immediately, and the government to increase education on AJB’s importance.